Bonding performance of melamine-urea–formaldehyde and phenol-resorcinol–formaldehyde adhesive glulams at elevated temperatures. (April 2020) - Liu, Jian; Yue, Kong; Xu, Liqin; Wu, Jinhao; Chen, Zhangjing; Wang, Lu; Liu, Weiqing; Lu, Weidong
Abstract: To better understand the bonding performance of glued laminated timbers (i.e., glulams) during fires, phenol–resorcinol–formaldehyde (PRF) and melamine–urea–formaldehyde (MUF) adhesives were used to investigate the effects of elevated temperatures on the glueline shear strength. The wood failure mode was observed to study the heat resistance of the two adhesives. Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) were used to analyze chemical and microscopic changes at various temperatures. The parallel-to-grain shear strength of solid larch wood decreased linearly with increasing temperature. Bonding strength of the wood–PRF glueline exposed to elevated temperatures was similar to that of the solid wood. The wood–MUF glueline exhibited good bonding performance at room temperature but showed poor thermal resistance. Shear strength of wood–MUF glueline was 0 MPa at 280 °C. Bonding performances of PRF and MUF deteriorated linearly with increasing temperature. FTIR analysis showed that PRF could maintain a relatively intact chemical structure when the temperature was higher than 150 °C, and the structure of the MUF degraded significantly when the temperature was higher than 200 °C.